Effects of the neonatal intensive care environment on circadian health and development of preterm infants - Van Gilst, D.; Puchkina, A. V.; Roelants, J. A.; Kervezee, L.; Dudink, J.; Reiss, I. K. M.; Van Der Horst, G. T. J.; Vermeulen, M. J.; Chaves, I. (Frontiers in Physiology, 2023)
The circadian system in mammals ensures adaptation to the light-dark cycle on Earth and imposes 24-hour rhythmicity on metabolic, physiological and behavioral processes. The central circadian pacemaker is located in the brain and is entrained by environmental signals called Zeitgebers. From here, neural, humoral and systemic signals drive rhythms in peripheral clocks in nearly every mammalian tissue. During pregnancy, disruption of the complex interplay between the mother's rhythmic signals and the fetal developing circadian system can lead to long-term health consequences in the offspring. When an infant is born very preterm, it loses the temporal signals received from the mother prematurely and becomes totally dependent on 24/7 care in the Neonatal Intensive Care Unit (NICU), where day/night rhythmicity is usually blurred. In this literature review, we provide an overview of the fetal and neonatal development of the circadian system, and short-term consequences of disruption of this process as occurs in the NICU environment. Moreover, we provide a theoretical and molecular framework of how this disruption could lead to later-life disease. Finally, we discuss studies that aim to improve health outcomes after preterm birth by studying the effects of enhancing rhythmicity in light and noise exposure.